Clay mineralogy and soil fertility of banana plantation alluvial soils at Costa Rica’s Caribbean lowlands - Arias, Fulvio (2009)
This paper analy-ses the relationship between soil clay mineralogy classes and soil fertility characteristics of soils cultivated with banana in the Caribbean low-lands of Costa Rica. The results corroborate that some fertility properties are closely related to the amount and type of dominant clay of the soils; among these characteristics the most relevant are CEC, phosphate retention and exchangeable cations. Soils belonging to the esmectitic clay mineralogy class showed greater values of CEC and exchangeable bases but lower phosphorus retention than soils of the metahalloysitic clay mineralogy class. Soil dominated by vermiculite showed lower amounts of available K and larger amounts of exchangeable Mg.